2008
DOI: 10.1002/ptr.2499
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical toxicological assessment of a phytotherapeutic product – CPV (based on dry extracts of Crataegus oxyacantha L., Passiflora incarnata L., and Valeriana officinalis L.)

Abstract: Associations of plants have been widely used, for centuries, in Ayurveda and in Chinese medicine and have been increasingly acknowledged in Western medicine. The objective of this study is to assess the level of toxicity of an association of three plants: Crataegus oxyacantha, Passiflora incarnata, and Valeriana officinalis (CPV extract). This association was administered to rats, mice, and dogs, both acute and chronically for 180 days. The tests used in the acute experiments were: observational pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Our study also demonstrated that the TA98 strain, after extract metabolism by S9 fraction, induced a significant increase in number of revertant colonies, indicating that the chemical components of the extract, after undergoing metabolism, might form mutagenic products capable of inducing insertion and/or deletion of DNA base pairs (frameshift mutations). Tabach et al (2009) developed a preclinical toxicological evaluation of a phytotherapeutic product termed CPV, which consists of C. oxyacantha aerial part extract (26.7 %) in association with Passiflora incarnata (33.3 %) and Valeriana officinalis (40 %) extracts. Several parameters were investigated in their study including, teratogenicity, mutagenicity, and genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study also demonstrated that the TA98 strain, after extract metabolism by S9 fraction, induced a significant increase in number of revertant colonies, indicating that the chemical components of the extract, after undergoing metabolism, might form mutagenic products capable of inducing insertion and/or deletion of DNA base pairs (frameshift mutations). Tabach et al (2009) developed a preclinical toxicological evaluation of a phytotherapeutic product termed CPV, which consists of C. oxyacantha aerial part extract (26.7 %) in association with Passiflora incarnata (33.3 %) and Valeriana officinalis (40 %) extracts. Several parameters were investigated in their study including, teratogenicity, mutagenicity, and genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…At present, few studies examined the genetic toxicity of C. oxyacantha extract. Tabach et al (2009) developed a preclinical toxicological assessment of a phytotherapeutic product-CPV, which consist of dry aerial parts of C. oxyacantha (26.7%), Passiflora incarnata (33.3%), and Valeriana officinalis (40%). The parameters assessed included weight, behavior, estrous cycle, teratogenicity in dogs, rats, or mice, and mutagenicity in bacteria (Ames test).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various species of Passiflora have aphrodisiac activity [56-60], and Myristica fragrans as well as Syzygium aromaticum [61,62], and extracts of Lantana camara [63,64] and Pilea spp. [23] fulfil the same purpose, while Portulaca oleracea showed efficacy in relieving uterine bleeding [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Various species of Passiflora have aphrodisiac activity [488491], and Myristica fragrans as well as Syzygium aromaticum [492], and extracts of Lantana camara [493, 494] and Pilea spp. [369] fulfil the same purpose, while Portulaca oleracea showed efficacy in relieving uterine bleeding [495, 496].…”
Section: Two Decades Of Traditional Medicine Research In Northern mentioning
confidence: 99%